1999
DOI: 10.1523/jneurosci.19-02-00630.1999
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding of Tropane-Based Photoaffinity Ligands on the Dopamine Transporter

Abstract: Benztropine and its analogs are tropane ring-containing dopamine uptake inhibitors that produce behavioral effects markedly different from cocaine and other dopamine transporter blockers. We investigated the benztropine binding site on dopamine transporters by covalently attaching a benztropine-based photoaffinity ligand, 125 I]RTI 82 occurs closer to the C terminal in a domain containing transmembrane helices 4-7. Thus, although benztropine and cocaine both contain tropane rings, their binding sites are disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 40 publications
8
72
0
Order By: Relevance
“…Our group has shown that structurally different irreversible DAT uptake blockers become incorporated into TMs 1 to 2, 4 to 6, or both regions (Vaughan et al, 1999Vaughan and Kuhar, 1996), consistent with these domains being in close proximity. Together these studies indicate that residues contributing to active sites on DAT for transport or inhibitor binding are found throughout the primary sequence in regions that flank EL2 but are juxtaposed in the native protein.…”
Section: The Dopamine Transporter (Dat) Is a Nasupporting
confidence: 55%
“…Our group has shown that structurally different irreversible DAT uptake blockers become incorporated into TMs 1 to 2, 4 to 6, or both regions (Vaughan et al, 1999Vaughan and Kuhar, 1996), consistent with these domains being in close proximity. Together these studies indicate that residues contributing to active sites on DAT for transport or inhibitor binding are found throughout the primary sequence in regions that flank EL2 but are juxtaposed in the native protein.…”
Section: The Dopamine Transporter (Dat) Is a Nasupporting
confidence: 55%
“…Finally, subsequent proteolysis of wild-type DAT protein crosslinked to photoaffinity-radiolabeled analogs of benztropine and a GBR series compound yielded a radioactive polypeptide fragment containing TM domains 1 and 2. In contrast, a photoaffinity-radiolabeled WIN series compound lacking the diphenylmethoxy moiety yielded a DAT proteolysis fragment that included TM domains 4 to 7 (Vaughan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated multiple-site binding for cocaine analogs (Madras et al 1989b;Izenwasser et al 1993) and the existence of two binding sites on the cloned (Boja et al 1992;Pristupa et al 1994;Eshleman et al 1995) and solubilized (Gracz and Madras 1995) dopamine transporter. It has also been suggested that mazindol and GBR12935 may bind to a different site on the dopamine transporter than cocaine (Berger et al 1990), and that there are differences in the binding domains of the GBR12935 analog, DEEP, or the benztropine analog, GAII-34, and cocaine (Vaughan et al 1999). These studies suggest that the heterogeneity of dopamine transporter binding may be related to the existence of two sites on, or states of, a single protein.…”
Section: Introductionmentioning
confidence: 99%